Quick evolution of edge-shared metal-oxygen octahedrons for boosting acidic water oxidation. (November 2022) - Zhang, Xiuxiu; Su, Hui; Sun, Xuan; Yang, Chenyu; Li, Yuanli; Zhang, Hui; Zhou, Wanlin; Liu, Meihuan; Cheng, Weiren; Wang, Chao; Wang, Huijuan; Liu, Qinghua
Abstract: Exploring highly durable and active electrocatalysts for water oxidation in acidic electrolytes remains a great challenge, because of the easy dissolution of active sites under harsh working conditions. Maintaining the coordination structure of active sites in the process of acidic oxygen evolution reaction (OER) to resist local active sites dissolution is theoretically viable, but rarely reported. Here, a new type of iridium-based oxide Cr-SrIrO3 with body-centered cubic structure (BCC-Cr-SrIrO3 ) is designed for boosting acidic-OER. Thanks to this unique atomic structure, an amorphous layer of CrIrOx with edge-shared CrOx and IrOx octahedrons was in situ formed by quick leaching of only Sr over BCC-Cr-SrIrO3 during the OER process. The edge-shared metal-oxygen octahedrons act as a tunable catalytic platform to optimize the acidic-OER, where the electron synergistic coupling effect between bimetallic octahedrons improves the OER activity by tens of times per iridium site with a mass activity of 417.6 A gIr −1 at 0.3 V overpotential; while the strong coordination persistence of iridium sites in the edge-shared octahedrons under working potentials dictates superior durability with a large stability number of 7 × 10 5 in 0.1 M HClO4 . This study promises a new route for the design of superior iridium-based acidic-OER catalysts. Graphical Abstract: A new type of Cr-SrIrO3 with abundant edge-shared IrOx and CrOx octahedrons was designed as an efficient OER electrocatalyst in acidic solutions. In combination with the in situ X-ray absorption spectroscopy characterizations, the electron synergistic coupling effect of bimetallic CrIr and the strong coordination persistence of Ir sites under working potentials are responsible for the observed high activity and stability. ga1 Highlights: Iridium-based oxide with edge-shared IrOx and CrOx octahedrons was designed as an efficient OER electrocatalyst. An amorphous layer of CrIrOx is in situ formed by quick leaching of only Sr over BCC-Cr-SrIrO3 during the OER process. The electron synergistic coupling and the coordination persistence of Ir sites endow the catalyst with high performance.